Probabilistic Seismic Hazard Analysis (PSHA) of Bali Airport Considering Earthquake Effects - Fazli Elahi; Hanindya Kusuma Artati; Achmed Pusha Agung; Vinda Nurul Hidayatul Aiman; Mohammad Subhan Rehman; Irfan Ullah (Universitas Negeri Semarang, 2026)
I Gusti Ngurah Rai International Airport in Bali is a critical national infrastructure located in a region of high seismicity driven by the Indo-Australian–Eurasian plate convergence. Despite the availability of national-level hazard maps, no site-specific probabilistic seismic hazard study incorporating local soil amplification has previously been conducted for this facility. This study performs site-specific Probabilistic Seismic Hazard Analysis (PSHA) using EZ-FRISK, one-dimensional non-linear soil amplification analysis using DEEPSOIL V7, and spectral matching of ground motions from the PEER NGA database to represent Bali seismic conditions. Historical earthquake data (Mw 4.0–9.0, 1900–2025) within a 500 km radius were compiled from the USGS catalog. Earthquake recurrence was characterized using the Gutenberg-Richter relationship. The Atkinson and Boore (2003) GMPE was applied for subduction sources. Bedrock PGA was determined at a 2% probability of exceedance in 50 years (return period = 2,475 years). Site response analysis was performed using N-SPT-derived shear-wave velocity profiles. Bedrock PGA is 0.308 g (design value 0.206 g after 2/3 factor). After nonlinear soil amplification, the surface PGA reaches 0.800 g, a 2.6-fold amplification, indicating a severe surface hazard. Hazard deaggregation identifies a dominant scenario earthquake of Mw 5.95 at 23.86 km. This is the first integrated PSHA study combining bedrock hazard, soil amplification, and spectral matching for Bali Airport, providing site-specific ground-motion parameters critical for earthquake-resistant structural design and liquefaction risk assessment at this strategically vital facility.